Does Hepatitis C Virus Infection Increase Risk for Stroke? A Population-Based Cohort Study - Liao, Chien-Chang (Public Library of Science, 2012)
BACKGROUND: The relationship between hepatitis C virus infection and risk of stroke remains inconsistent. This study evaluates the risk of stroke in association with chronic hepatitis C infection in a longitudinal population-based cohort. METHODS: We identified 4,094 adults newly diagnosed with hepatitis C infection in 2002–2004 from the Taiwan National Health Insurance Research Database. Comparison group consisted of 16,376 adults without hepatitis C infection randomly selected from the same dataset, frequency matched by age and sex. Events of stroke from 2002–2008 were ascertained from medical claims (International Classification of Diseases, Ninth Revision, Clinical Modification, ICD-9-CM, codes 430–438). Multivariate adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated for potential associated factors including HCV infection, age, sex, low-income status, urbanization, cessation of cigarette smoking, alcohol-related illness, obesity, history of chronic diseases and medication use. FINDINGS: During 96,752 person-years of follow-up, there were 1981 newly diagnosed stroke cases. The HRs of stroke associated with medical conditions such as hypertension, diabetes and heart disease were 1.48 (95% CI 1.33 to 1.65), 1.23 (95% CI 1.11 to 1.36) and 1.17 (95% CI 1.06 to 1.30), respectively, after adjustment for covariates. The cumulative risk of stroke for people with hepatitis C and without hepatitis C infections was 2.5% and 1.9%, respectively (p<0.0001). Compared with people without hepatitis C infection, the adjusted HR of stroke was 1.27 (95% CI 1.14 to 1.41) for people with hepatitis C infection. CONCLUSION: Chronic hepatitis C infection increases stroke risk and should be considered an important and independent risk factor.